2021
DOI: 10.3347/kjp.2021.59.5.531
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Intensity of Opisthorchis viverrini Metacercarial Infection in Fish from Phnom Penh, Takeo, and Kandal Provinces, Cambodia

Abstract: The prevalence and intensity of Opisthorchis viverrini metacercariae (OvMc) were investigated in fish from 3 southern administrative regions along the Mekong River in Cambodia, i.e., Phnom Penh, Takeo, and Kandal Provinces from 2017 to 2020. A total of 295 freshwater fish (24 species) were transported to our laboratory with ice and examined using the artificial digestion method. In Phnom Penh, among 4 fish species positive for OvMc, 9 (23.7%) of 38 specimens examined were infected, and their intensity of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Three freshwater fish species are usually consumed of raw by villagers in Kratie Province; thus, they are thought to facilitate O. viverrini infections (Sohn et al, 2012). The prevalence of O. viverrini metacercariae (OvMc) in fish from 3 southern areas in Cambodia along the Mekong River has been reported, including that in Phnom Penh (23.7%), Takeo (38.1%), and Kandal (90.2%) Provinces, with 4, 10, and 6 fish species positive for OvMc, respectively (Sohn et al, 2021). Moreover, OvMc is most prevalent in workers and rural inhabitants of Lower Myanmar who consumed raw cyprinoid fish (Aung et al, 2017); scientific evidence has revealed that the consumption of raw freshwater fish is a major risk factor for human liver fluke infection (Chavengkun et al, 2016;Kaewpitoon et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three freshwater fish species are usually consumed of raw by villagers in Kratie Province; thus, they are thought to facilitate O. viverrini infections (Sohn et al, 2012). The prevalence of O. viverrini metacercariae (OvMc) in fish from 3 southern areas in Cambodia along the Mekong River has been reported, including that in Phnom Penh (23.7%), Takeo (38.1%), and Kandal (90.2%) Provinces, with 4, 10, and 6 fish species positive for OvMc, respectively (Sohn et al, 2021). Moreover, OvMc is most prevalent in workers and rural inhabitants of Lower Myanmar who consumed raw cyprinoid fish (Aung et al, 2017); scientific evidence has revealed that the consumption of raw freshwater fish is a major risk factor for human liver fluke infection (Chavengkun et al, 2016;Kaewpitoon et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported on the prevalence of intestinal helminth infections among villages in Kratie Province, northeastern Cambodia, using fecal specimens and the Kato-Katz thick smear technique. The highest prevalence of Opisthorchis viverrini infections occurred in Roka Kandal A (10.4%), followed by Talous (5.9%); in both these villages, adult residents presented with a higher prevalence (19.4% and 9.0%, respectively) than schoolchildren (6.4% and 1.4%) (Sohn et al, 2021). Moreover, Strongyloides stercoralis and hookworm or soil-transmitted helminth were high prevalence in Preah Vihear Province, northeastern Cambodia.…”
Section: Introductionmentioning
confidence: 95%